A new measuring approach in assessing hamstring flexibility: Reliability, validity, and applicability of ısolated hamstring flexibility test - Talu, Yasin; Tuncer, Aysenur; Talu, Burcu (Lippincott Williams and Wilkins)
Objective:This study was planned to determine the reliability, validity, and applicability of the isolated hamstring flexibility test (IHFT).Design:A cohort study (diagnosis); level of evidence, 2.Setting:It was performed in the research and application laboratory.Participants:Seventy-five individuals aged 18 to 25 years, selected through simple probability random sampling, with a normal Beighton Horan and Joint Mobility Index scores, and who volunteered to participate, were included for evaluation.Interventions:On then first and third days, participants underwent muscle strength, sit-and-reach test, active knee extension test, IHFT for validity and reliability. Stretching exercises were prescribed as a home program for 31 patients with limited knee extension, and measurements were repeated at the end of the eighth week.Main outcome measures:Sit-and-reach test, active knee extension test, IHFT.Results:The test-retest reliability was high (intraclass correlation coefficient, 0.993). Our test demonstrated validity when compared in terms of flexibility gained. A significant difference was found between pre-post stretching exercise training in all 3 tests (P < 0.05).Conclusion:It was observed that the IHFT is reliable and applicable in determining hamstring flexibility. Given the absence of another test specifically measuring hamstring flexibility in isolation, its indirect validity was established through analysis with other tests using the gold standard for assessing gains in hamstring flexibility. © Copyright 2024 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: elasticity; flexibility; hamstring; stretching